(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
The current study aimed to study the effect of adding aqueous extracts of lemongrass and bay leaves at concentrations (1-0.5%) on the chemical composition and microbial properties of camel burgers preserved in freezing at (-18°C) and for preservation periods (0-2-4-6) weeks. The results showed that there were no significant differences at the level (p <0.05) when studying the chemical composition of the camel burger preserved in freezing at a temperature of (-18°C) and for periods of preservation (0-2-4-6) a week, as it was noted that the protein content increased In addition to that when studying the microbial tests, a significant decrease was observed at the level (p><0.05) for the numbers of total bacteria, cold-loving bacteria and colon bacteria for camel burgers preserved in freezing (-18°C) and for preservation periods of (0-2-4-6) a week>